Intermediate accounting - Nikolai, Loren A.; Bazley, John D. (Cincinnati, OH : South-Western College, 2000)
This book is divided into five parts: Concepts, financial statements, and related disclosures; Asset measurement and income determination; Valuation of liabilities and investments; Stockholders' equity; and Special topics about Financial reporting.
Keywords: Accounting; Accounting